Intracellular localization of Borrelia burgdorferi within human endothelial cells. - Ma, Y (1991)
The later stages of infection by the Lyme disease pathogen, Borrelia burgdorferi, are characterized by the persistence of the organism in individuals possessing a strong anti-Borrelia immune response. This suggests that the organism is sequestered in a tissue protected from the immune system of the host or there is a reservoir of the organism residing within the cells of the host. In this report, the ability of B. burgdorferi to gain entrance into human umbilical vein endothelial cells was explored as a model for invasion. Incubation of B. burgdorferi with human umbilical vein endothelial cells at ratios ranging from 200:1 to 5,000:1 resulted in the intracellular localization of 10 to 25% of B. burgdorferi in 24 h. The intracellular location of the spirochetes was demonstrated by the incorporation of radiolabeled B. burgdorferi into a trypsin-resistant compartment and was confirmed by double-immunofluorescence staining which differentiated intracellular from extracellular organisms. Actin-containing microfilaments were required for the intracellular localization, indicating that the host cell participates in the internalization process. Activation of endothelial cells by agents known to increase the expression of several adhesion molecules had no effect on the interaction of B. burgdorferi with the endothelial monolayer. This indicates that the endothelial receptor for B. burgdorferi is constitutively expressed and that internalization is not dependent upon adhesion molecules whose expression is induced by inflammatory mediators. The demonstration of B. burgdorferi within endothelial cells suggest that intracellular localization may be a potential mechanism by which the organism escapes from the immune response of the host and may contribute to persistence of the organism during the later stages of Lyme disease.